Hydrogen diffusion process in the oxides formed on zirconium alloys during corrosion in pressurized water reactor conditions. (15th February 2017) - Tupin, Marc; Martin, Frantz; Bisor, Caroline; Verlet, Romain; Bossis, Philippe; Chene, Jacques; Jomard, François; Berger, Pascal; Pascal, Serge; Nuns, Nicolas
Highlights: The oxide film in pre-transition is divided into two sub-layers, an external one, highly permeable to hydrogen and an inner protective one. The pre-transition oxide layer presents two H-oxide interaction sites in consistency with the subdivision of the oxide layer. Apparent diffusion coefficient of hydrogen in the inner oxide was estimated around 2.10 −14 cm 2 /s at 360 °C. Abstract: During the corrosion in primary water of zirconium alloys, a fraction of hydrogen from the water diffuses through the oxide into the alloy. To better understand the hydriding process, isotopic tracers and SIMS experiments were performed on oxides grown on Zircaloy-4 alloy under simulated primary water conditions. Results showed the oxide film in pre-transition is divided into two sub-layers, an external one, highly permeable to hydrogen and an inner protective one. Thermal Desorption Spectroscopy analyses revealed two interaction sites of hydrogen, located in each oxide sublayer. Apparent diffusion coefficients of hydrogen in both oxide sublayers were estimated with different methods.